2010
DOI: 10.1073/pnas.1015954107
|View full text |Cite
|
Sign up to set email alerts
|

Elements between the IgH variable (V) and diversity (D) clusters influence antisense transcription and lineage-specific V(D)J recombination

Abstract: Ig and T-cell receptor (TCR) variable-region gene exons are assembled from component variable (V), diversity (D) and joining (J) gene segments during early B and T cell development. The RAG1/2 endonuclease initiates V(D)J recombination by introducing DNA double-strand breaks at borders of the germ-line segments. In mice, the Ig heavy-chain (IgH) locus contains, from 5′ to 3′, several hundred V H gene segments, 13 D segments, and 4 J H segments within a several megabase region. In developing B cells, IgH variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
0
26
1
3
Order By: Relevance
“…Surprisingly, we found an increase in antisense transcription from the Adam6 gene through the DSP genes, suggesting a broader regulatory role for CTCF/DFL. Indeed, a very recent study has shown that deletion of a 108-kb intergenic region extending from the proximal V H genes through DFL16.1, including the CTCF/DFL sites, resulted in increased D H antisense transcription throughout the D H locus in both B and T cells (25). Because we have shown that CTCF knockdown results in the same increase in D H antisense transcription, we propose it is the decrease in looping at CTCF/DFL-Eμ-CTCF/3′RR that mediates this enhancing effect on D H antisense transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we found an increase in antisense transcription from the Adam6 gene through the DSP genes, suggesting a broader regulatory role for CTCF/DFL. Indeed, a very recent study has shown that deletion of a 108-kb intergenic region extending from the proximal V H genes through DFL16.1, including the CTCF/DFL sites, resulted in increased D H antisense transcription throughout the D H locus in both B and T cells (25). Because we have shown that CTCF knockdown results in the same increase in D H antisense transcription, we propose it is the decrease in looping at CTCF/DFL-Eμ-CTCF/3′RR that mediates this enhancing effect on D H antisense transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense transcription through the D H locus precedes D H -to-J H rearrangement and has been proposed to make the D H region accessible for subsequent rearrangement (23,24). Some antisense transcription begins near Eμ and is dependent on the presence of Eμ, whereas other antisense transcription begins near DST4 (23,25). Recently, it was shown that antisense transcription decreases just upstream of the CTCF/DFL sites, suggesting that this CTCF region is a boundary that prevents antisense transcription from continuing toward the V H locus (22).…”
Section: Loss Of Ctcf and Rad21 Has An Impact On Long-range Chromosomalmentioning
confidence: 99%
“…Este proceso se conoce como rearreglo o reordenamiento, términos que se utilizarán indistintamente en este texto. Cuando el reordenamiento de los genes del receptor de antígeno no es perfecto, bien sea por falta de alguna enzima o por otro defecto, se presentan graves inmunodeficiencias (13). Por otra parte, cuando una célula linfoide se transforma en cancerosa y se divide sin cesar, sus células hijas poseen el mismo reordenamiento de los genes de receptor de antígeno que la célula madre que las originó.…”
Section: Evaluación De Los Reordenamientos De Genes Del Receptor Del unclassified
“…El segmento D solo está presente en los loci de las cadenas pesadas de Ig y los loci β y δ son exclusivos de las del TCR (figura 2). La recombinación alélica ocurre cuando se unen los fragmentos variables, de diversidad y unión, llamada recombinación V(D)J que se regula por medio de exclusión alélica; una vez que un alelo se ha reordenado, se envía una señal al otro para interrumpir el proceso (12,13). Los reordenamientos se efectúan por medio de pasos secuenciales e invariables:…”
Section: Evaluación De Los Reordenamientos De Genes Del Receptor Del unclassified
See 1 more Smart Citation